Phytochemical study and subacute toxicity in vivo evaluation of Phyllanthus odontadenius (Phyllanthaceae) aqueous extracts - NSENDO , MUANGU-KABI Oscar; Kikakedimau Nakweti, Rufin; Mbozo, Makinutewa Alain; TABA, Kalulu-Muzele; Ngbolua, Koto-Te-Nyiwa; LUYINDULA, NDIKU Sébastien (Orapuh Journal, 2025)
Introduction Phyllanthus odontadenius is recognised for its rich composition of natural substances, notably secondary metabolites, which offer promising applications in pharmacology and the food industry.Purpose This study sought to identify the major secondary metabolites present in P. odontadenius and to assess the in vivo subacute toxicity of its aqueous extracts.Methods Aqueous and methanolic extracts of P. odontadenius samples collected from Kinshasa, Kongo-Central, and Kwango (Democratic Republic of the Congo) were subjected to phytochemical screening and thin-layer chromatography (TLC). Subacute toxicity of the aqueous extract was evaluated in Wistar albino rats administered 500 mg/kg body weight via oral gavage for 14 consecutive days. Body weights were measured before and after treatment. Post-treatment, the weights of the liver, heart, and kidneys were recorded, and biochemical markers (urea, creatinine, AST, ALT, GGT, and ALP) were analysed.Results Phytochemical analysis confirmed the presence of alkaloids, polyphenols, flavonoids, terpenes, anthocyanins, and steroids, while saponins were absent. A notable increase in body weight was observed in all rats. Organ weights varied across extract sources, with the liver from the Kenge group showing the highest weight (4.23 ± 0.04 g). Biochemical profiles showed slight to marked elevations in liver enzymes and kidney markers across treatment groups compared to controls. Particularly, the Kenge extract group recorded the highest AST (322.00 ± 36.68 U/L) and ALP (431.4 ± 32.23 U/L) levels, suggesting possible hepatic stress or damage.ConclusionAlthough P. odontadenius is traditionally used in herbal medicine, findings from this study suggest that chronic use of its aqueous extract may pose risks to sensitive organs, especially the liver. Further studies, including histological analysis and isolation of potential toxic constituents, are recommended to support its safe use.